Effectiveness of a Brief Diabetes Risk Assessment Instrument for Detecting Undiagnosed Type 2 Diabetes Among High-Risk Ethnic Communities in West Africa - Alaofè, Halimatou; AMOUSSA HOUNKPATIN, WALIOU BODOUNRIN AYANDA (My University, 2023)
Background & Objectives: With the growing burden of type 2 diabetes (T2D) and associated health, social, and economic costs in sub-Saharan Africa, tools are needed to assess T2D risks rapidly, allowing for targeted early intervention. The objective of this study was to assess the effectiveness of a brief diabetes risk assessment instrument for detecting undiagnosed Type 2 Diabetes among high-risk ethnic communities in Benin, West Africa. Methods: Between October-November 2022, data were collected from 270 adults of 18 years and older in six high-risk diabetes departments of Benin using the Prediabetes Detection and Physical Activity Intervention Delivery (PRE-PAID) risk assessment instrument and assessing hemoglobin A1c (HbA1c). ANOVA and linear regression were used to assess correlation between reported instrument data and HbA1c. We also calculated the PRE-PAID performance regarding sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and area under the receiver operator curve (AUC) in predicting dysglycemia based on HbA1c ≥ 5.7%. Conclusions. The PRE-PAID risk assessment instrument showed good performance in identifying prediabetes and T2D in high-risk ethnic communities of Benin, demonstrating that a risk assessment instrument can be an accurate, low-cost, Results: Mean (± SD) HbA1c and PRE-PAID scores were 5.88% ± 1.16 and 8.5 ± 4.1, respectively. Based on the risk assessment instrument results, ANOVA showed that HbA1c significantly increased with increasing risk classification (Welch Statistic 30.45, p < 0.001). Linear regression revealed that previous diagnoses of high blood sugar, BMI, physical activity, and age were significant contributors to the variance in HbA1c (p < 0.05). At a risk score of ≥ 6.5—the threshold for high risk set by the PRE-PAID—had sensitivity 82%, specificity 76%, PPV 55%, NPV 73%, and UAC 0.86. Conclusions. The PRE-PAID risk assessment instrument showed good performance in identifying prediabetes and T2D in high-risk ethnic communities of Benin, demonstrating that a risk assessment instrument can be an accurate, low-cost, educational, and time-efficient method for assessing T2D risk. Early detection of prediabetes and T2D is critical to increase awareness and prevent complications and their progression.
Keywords: Risk assessment tool; glycated hemoglobin (hba1c); prediabetes; diabetes; Benin.